1991
DOI: 10.1002/yea.320070407
|View full text |Cite
|
Sign up to set email alerts
|

Induction of a heat‐shock‐type response in Saccharomyces cerevisiae following glucose limitation

Abstract: The protein pattern of yeast cells which have arrested proliferation in response to glucose exhaustion is drastically different from that of exponentially growing cells (Boucherie, 1985). In this study, we used two-dimensional gel electrophoresis to characterize the protein events responsible for these alterations. We found that the induction of heat-shock proteins is one of the major events responsible for these changes. This induction accounts for the synthesis of 18 of the 35 novel polypeptides observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
22
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 44 publications
(33 reference statements)
2
22
0
Order By: Relevance
“…Several studies revealed major changes in the pattern of gene expression, with the common feature that genes encoding components of the glycolytic pathway and cell growth machinery are repressed, and glucose-repressed genes are de-repressed (Bataillé et al, 1991;Boucherie, 1985;Boy-Marcotte et al, 1987;DeRisi et al, 1997). However, a subset of genes that is characteristic for this phase was already induced when glucose and all other nutrients were still available in the medium, and expression was induced far in advance of other so-called diauxic and stationary phase events (Herman, 2002;Werner-Washburne et al, 1993, 1996.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies revealed major changes in the pattern of gene expression, with the common feature that genes encoding components of the glycolytic pathway and cell growth machinery are repressed, and glucose-repressed genes are de-repressed (Bataillé et al, 1991;Boucherie, 1985;Boy-Marcotte et al, 1987;DeRisi et al, 1997). However, a subset of genes that is characteristic for this phase was already induced when glucose and all other nutrients were still available in the medium, and expression was induced far in advance of other so-called diauxic and stationary phase events (Herman, 2002;Werner-Washburne et al, 1993, 1996.…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional limitation causes cells to arrest cell growth and enter stationary phase (1)(2)(3). This is a metabolically quiescent state where expression of genes required for survival is induced, whereas expression of cell cycle genes is repressed (4,5). Fission yeast cells enter stationary phase from G 2 upon glucose starvation and from G 1 upon nitrogen starvation (6).…”
mentioning
confidence: 99%
“…Once rapid growth begins, after lag phase, energy is derived primarily from fermentation of glucose. When glucose is exhausted, a transient growth arrest occurs (the diauxic shift), during which time cells adapt to respiratory metabolism (5,30,66). After this arrest, cells grow at a much lower rate for several days prior to entering stationary phase (17,30).…”
mentioning
confidence: 99%
“…Stationary phase, defined as the time when there ceases to be a net increase in cell number, is a differentiated state (75,76) during which cells enter a genetically defined offshoot of the cell cycle (41). The synthesis of most postexponential proteins in S. cerevisiae is initiated during the diauxic shift (5,30). In dramatic contrast, synthesis of one protein, Snz1p (previously designated p35) is detected much later than other proteins (30).…”
mentioning
confidence: 99%